Nandrolone Decanoate and Physical Effort: Histological and Morphometrical Assessment in Adult Rat Uterus - de Almeida Chuffa, Luiz Gustavo [UNESP]; de Souza, Roberta Barreiros [UNESP]; Frei, Fernando [UNESP]; Paccola Mesquita, Suzana de Fatima; Camargo, Isabel Cristina Cherici [UNESP] (Wiley-liss, 2011)
In the past decades, the therapeutic use of anabolic androgenic steroids (AAS) has been overshadowed by illicit abuse of these drugs by athletes and non-athletes. Since that AAS can affect the reproductive tract, resulting in reproduction and fertilization damages, the purpose of this study was to investigate the nandrolone decanoate (ND) effects, associated or not with physical effort, on the uterine histomorphometric parameters. Female Wistar rats, sedentary or not, were exposed to treatment with ND by intraperitoneal injection (5 mg/kg/day, once a week) during four consecutive weeks. Control animals, sedentary or not, received vehicle alone (propylene glycol) in the same manner. The physical activity was forced swimming (20 min/day). During the experiment, all animals were monitored by daily vaginal smears. After 30 days of treatment, the females were sacrificed and their uteri collected and examined under light microscopy techniques. The ND-treated females showed estrus acyclicity and decreased thickness of both the epithelium and endometrial stroma. A reduction in the number and size of blood vessels was also found in ND-treated rats submitted to physical effort when compared to ND sedentary rats. ND-treated rats, regardless of exercise, exhibited stromal fibrosis and reduced gland ducts that displayed high mitotic activity. A remarkable widespread presence of leukocytes occurred in rats receiving ND and submitted to exercise. These results suggest that ND associated or not with physical effort causes histomorphometric changes to the rat uterus. Anat Rec, 294:335-341, 2011. (C) 2010 Wiley-Liss, Inc.
Keywords: nandrolone decanoate; steroids; uterus; histology; exercise; rat